Kesediaan Mahasiswa UNNES (Universitas Negeri Semarang) Melakukan Vaksinasi Covid-19 - Aulia Khoirunisa; Chatila Maharani (Jurnal Kesehatan Masyarakat, 2022)
Background: To overcome the Covid-19 pandemic, the Government set regulations for the procurement and implementation of vaccinations, but when it was implemented, it caused various public responses. There are people who are willing or unwilling to be vaccinated against Covid-19. This research was conducted on UNNES students because UNNES is one of the universities in Semarang and Semarang is the city with the highest number of confirmed cases of Covid-19 in Central Java. Purpose: Knowing the factors related to the willingness of UNNES students to vaccinate against Covid-19. Methods: Using quantitative design through a questionnaire instrument (googleform) which distributed online to UNNES students. From the collected data, univariate and bivariate analysis was carried out. Bivariate analysis uses the Fisher's Exact Test as an alternative to the Chi Square Test with the SPSS application. Results: This research shows that the willingness of UNNES students to vaccinate against Covid-19 is related to attitudes, values/ beliefs, family support, and government policies. While the unrelated factors are knowledge, perception of distance and ease of information. The reasons WHY UNNES students are not willing to be vaccinated include not believing in the Covid-19 vaccine, doubting the halalness, effectiveness of the vaccine, fear of the side effects caused and so on. Conclusion: Factors related to willingness to vaccinate are attitudes, values/ beliefs, family support, and government policies while factors that are not related to willingness to do vaccines are knowledge, perception of distance and ease of information.